ANALISIS PENGARUH PENGETAHUAN, TATA KELOLA PERUSAHAAN TERHADAP SAHAM SYARIAH DALAM PERSPEKTIP ISLAM DENGAN PENDEKATAN CIRCULAR CAUSATION DI BURSA EFEK INDONESIA - Hotman Tohir Pohan (Media Riset Akuntansi, Auditing & Informasi, 2014)
The aim of this research is to prove and analyze the effects of knowledgeand corporate governance to sharia stocks. Moreover, the background of the research is based on the different philosophy between mainstream corporate governance and Islamic corporate governance. The methodology of this research applies to circular causation approach which the variables are endogeneity and reciprocal effects. The results of the research are; firstly, it indicates that there are significant positive effects of knowledge to sharia stocks, sharia stocks to knowledge, knowledge to corporate governance, and corporate governance to knowledge.Secondly, there are significant negative effects of corporate governance to sharia stocks and sharia stocks to corporate governance. The reciprocal positif effects are the form of interaction which complements among variables which contain manfaah and mashlaha, whereas the reciprocal negative effects are the form of interaction among variables that contain dharar.